Religiosity and resilience in students of psychology at a private university in Lima East - Guevara Ccapa, Vasthi Paola (2019)
Objective: In this research the relationship between religiosity and resilience in a sample of 156 psychologystudents at 4 cycles, in a private university in Lima Este. Material and Methods: This research is correlational.Religiosity Scale (2014) was used and for the variable of resilience to evaluate religiousness variable, the scaleof resilience Wagnild and Young (1993). Participants are students of psychology at a private university in LimaEste, ages 18 to 30, comprising a non-probabilistic sample of 156 subjects of both sexes and of different religions.Results: The results show a moderately significant relationship between the dimensions of religiosity andresilience. It was determined that students with higher level students practice their religion, they have a higherlevel of resiliency. Conclusions: These results support the theoretical considerations determine religiosity as apartner in the formation of the resilience factor.